Highly active Fe-Co-Zn/K-Al2O3 catalysts for CO2 hydrogenation to light olefins - Witoon T.; Chaipraditgul N.; Numpilai T.; Lapkeatseree V.; Ayodele B.V.; Cheng C.K.; Siri-Nguan N.; Sornchamni T.; Limtrakul J. (Elsevier Ltd, 2023)
Aluminum compounds; Carbides; Carbon dioxide; Catalyst activity; Hydrogenation; Iron oxides; Light olefins; Paraffins; Zinc; Active site; CO2 hydrogenation; Function of time; Iron carbides; Light olefins yield; Number of active sites; Optimum operating conditions; Zn content; Zinc compounds